The Ethiopian Law on the Right to Confrontation - Mehretu, Alemu; Alemayehu, Awol (Bahir Dar University Journal of Law, 2023)
This article examines the Ethiopian law on the protection of the accused person’s right to confront prosecution witnesses. The accused is entitled to confront adverse witnesses so that not only the criminal justice process and its outcome become fair and reliable but also the accused enjoys a meaningful participation in the process. Yet, the right is not unbridled with the nature and scope of the restriction varying across jurisdictions depending on the interests and values pursued most. The most common restrictions are triggered by protection of vulnerable witnesses, the use of depositions of absent witnesses, trial in absentia and use of anonymous witnesses. This article argues that the administration of restrictions under the Ethiopian law suffers two general limitations. First, it raises issues of compatibility with the constitution. Second, the restrictions fall short of adequately counterbalancing the interests involved: that of the accused, the public, victims, and witnesses. Allowing witness statements made before the police and depositions of preliminary inquiry to be put in evidence at trial in the situation where the accused is not represented by legal counsel and is not entitled to cross-examine witnesses; allowing trial in absentia in broad range of crimes without adequate guarantees put in place; and use of hearsay evidence in the circumstances where it is not regulated, all threaten the right to confrontation.